Development of Interactive Multimedia Based Learning Media for Petanque Sports Extracurricular Development Course - Boby Helmi; Andi Nur Abady; Katon Cahyo Gumilang (Jurnal Pedagogi dan Pembelajaran, 2026)
The limited availability of interactive and contextual learning media in the Petanque Sports Extracurricular Development course has hindered the optimization of student engagement and learning outcomes. This study aimed to develop, evaluate the feasibility of, and examine the effectiveness of interactive digital multimedia-based learning media to improve the quality of petanque instruction. The study employed a Research and Development (R&D) approach using the Borg and Gall model. The research subjects included subject matter experts, media experts, petanque experts, and students involved in the small group, large group, and operational field trials. Data were collected through expert validation questionnaires, student response questionnaires, and learning achievement tests, and were analyzed using qualitative descriptive analysis, quantitative descriptive analysis, and the Independent Samples t-test. The results indicated that the developed learning media was rated as good during the initial validation and improved to excellent after revision. Student responses increased from 82.53% in the small-group trial to 92.33% in the large-group trial. The t-test results revealed a significant difference between the pretest and posttest scores (p < 0.05), demonstrating that the developed media effectively improved students' learning outcomes. This study concludes that the interactive digital multimedia-based learning media is feasible and effective for use in petanque instruction. These findings have implications for the development of more contextual multimedia-based learning in sports education.